The reliability, validity, and applicability of an English language version of the Mini-ICF-APP. - Molodynski, A; Linden, M; Juckel, G; Yeeles, K; Anderson, C; Vazquez-Montes, M; Burns, T (2013)
PURPOSE: This study aimed at establishing the validity and reliability of an English language version of the Mini-ICF-APP. METHODS: One hundred and five patients under the care of secondary mental health care services were assessed using the Mini-ICF-APP and several well-established measures of functioning and symptom severity. 47 (45 %) patients were interviewed on two occasions to ascertain test-retest reliability and 50 (48 %) were interviewed by two researchers simultaneously to determine the instrument's inter-rater reliability. Occupational and sick leave status were also recorded to assess construct validity. RESULTS: The Mini-ICF-APP was found to have substantial internal consistency (Chronbach's α 0.869-0.912) and all 13 items correlated highly with the total score. Analysis also showed that the Mini-ICF-APP had good test-retest (ICC 0.832) and inter-rater (ICC 0.886) reliability. No statistically significant association with length of sick leave was found, but the unemployed scored higher on the Mini ICF-APP than those in employment (mean 18.4, SD 9.1 vs. 9.4, SD 6.4, p < 0.001). The Mini-ICF-APP correlated highly with the other measures of illness severity and functioning considered in the study. CONCLUSIONS: The English version of the Mini-ICF-APP is a reliable and valid measure of disorders of capacity as defined by the International Classification of Functioning. Further work is necessary to establish whether the scale could be divided into sub scales which would allow the instrument to more sensitively measure an individual's specific impairments.